EFFECT OF SHYNESS ON EMOTIONAL INTELLIGENCE OF ADOLESCENTS - Gowda, H.M. Ramakrishne; D’Souza, Lancy; Nagendra, K.S (International Journal of Psychosocial Rehabilitation, 2020)
The present study reports the effect of emotional intelligence and shyness among respondents aged 13-21 years who were studying in and around Mysore city. A total of 915 studying in classes from VIII to PUC from English and Kannada medium were randomly selected for the study. They were administered Shyness Assessment Test (SAT) by D’Souza (2006) and emotional intelligence scale by Hyde, Pethe, and Dhar (2005). Two way ANOVA was employed to find out the significance of difference between shyness levels and developmental stages on emotional intelligence scores. Results revealed that shyness had significant influence on components of emotional intelligence- integrity value orientation, commitment, altruism and total emotional intelligence scores, as the shyness levels increased more or less emotional intelligence decreased linearly and significantly. In components self awareness, empathy, self motivation, emotional stability, Integrity, commitment and altruistic behaviour and in total emotional intelligence adolescents in early and middle stages had higher emotional intelligence compared to adolescents in late adolescent stage. Further, it was found that adolescents in early and middle adolescence stages with low and medium levels of shyness had least emotional intelligence, where as adolescents in late adolescence stages with high levels of shyness had least emotional intelligence scores